THE RELATIONSHIP BETWEEN THE PROVISION OF MILK FORMULA DIARRHEA IN BABY AGE 0-6 MONTHS IN VILLAGE NGIPANG RT 02 RW 28 WARD KADIPIRO DISTRICT BANJARSARI - Ardika, Noviyana Ayu; STIKES PKU Muhamdiyah Surakarta, Sugihartiningsih (Jurnal Kebidanan, 1970)
Noviana Ayu Ardika & Sugihartiningsih STIKES PKU Muhammadiyah Surakarta ABSTRACT Background: People in general have always considered it a case of diarrhea is trivial, whereas if you know what happened was a lot of diarrhea patients who experienced death. Diarrheal disease is a disease that must be treated because it can lead to severe dehydration and hypovolemic shock death in infants. From the preliminary study in rural Ngipang through interviews with 5 samples of 20 infants aged 0-6 months, showed 3 (60%) infants with diarrhea caused by milk formula and 2 (40%) were not caused by milk formula. Objective: To determine the relationship between formula feeding with diarrhea in infants aged 0-6 months in the village of Ngipang Rt 02 Rw 28 Kadipiro, District Banjarsari. Methods: This study used a quantitative description of the research study with the correlation method deshain cross sectional study. Sample of 10 babies using non-probability sampling technique. Research instrument in the form of check list. Data were analyzed with the Spearman Rank Correlation. Results: There was no relationship between formula feeding with diarrhea in infants aged 0-6 months of Ï = 0.571, p = 0.084> 0.05. Conclusion: frequency rate formula feeding no relation to the incidence of diarrhea in infants aged 0-6 months. Keywords: Infant formula, diarrhea, infants 0-6 months.